2012
DOI: 10.1161/circulationaha.111.055079
|View full text |Cite
|
Sign up to set email alerts
|

Net Clinical Benefit of Warfarin in Patients With Atrial Fibrillation

Abstract: Background— Known risk factors for bleeding during anticoagulant treatment are largely the same as those predicting thromboembolic events in patients with atrial fibrillation (AF). Our objective was to investigate how to maximize the likelihood of avoiding both stroke and bleeding. Methods and Results— All 182 678 subjects with atrial fibrillation in the Swedish Hospital Discharge Register were studied for an average of 1.5 years (260 000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
218
0
19

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 418 publications
(256 citation statements)
references
References 40 publications
19
218
0
19
Order By: Relevance
“…Anticoagulation reduces the thromboembolic risk by approximately two thirds, irrespective of baseline risk 1. However, the use of all antithrombotic agents increased the risk of bleeding, with intracranial hemorrhage being the most serious bleeding complication.…”
Section: Introductionmentioning
confidence: 99%
“…Anticoagulation reduces the thromboembolic risk by approximately two thirds, irrespective of baseline risk 1. However, the use of all antithrombotic agents increased the risk of bleeding, with intracranial hemorrhage being the most serious bleeding complication.…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for the lack of clinical impact by bleeding risks scores is partially because of the parallel nature of bleeding risk scores and stroke risk scores such as CHA2DS2‐VASc (Congestive heart failure, Hypertension, Age, Diabetes Mellitus, Prior Stroke, Vascular disease, Sex category) 11. For example, with increasing age, the risk of stroke and major bleeding increase.…”
mentioning
confidence: 99%
“…Friberg and colleagues showed that increased thromboembolism risk was associated with increased risk of bleeding, likely because many of the risk factors involved in the risk stratification scores overlap 11. In this study, the only patients who did not benefit from anticoagulation were patients with a CHA2DS2VASc score of 0 or 1, patients in whom anticoagulation is not recommended by either the European Society of Cardiology or AHA/ACC/HRS guidelines 1, 10, 11. In fact, a patient with a CHA2DS2VASc score of 5 and an HAS‐BLED score of 5 would have a net clinical benefit of 3% per year even when weighting intracranial hemorrhage as 1.5 times the clinical impact of a stroke 11.…”
mentioning
confidence: 99%
See 2 more Smart Citations